GAMBARAN INFEKSI CACING SOIL TRANSMITTED HELMINTH PADA MURID SD NEGERI 23 PASIR SEBELAH KOTO TANGAH TAHUN 2023 - Rahma Triyana; Muhammad Riandi; Dian Puspita; Ruhsyahadati, Ruhsyahadati; Nana Liana; Prima Adelin; Rifkind Malik; Roland Helmizar; Muhammad Rizki Saputra; Alief Dhuha (Nusantara Hasana Journal, 2025)
Soil-transmitted helminth (STH) infections remain a significant public health issue in developing countries, particularly among primary school children who are highly exposed to contaminated environments and often have inadequate personal hygiene practices. This study aimed to describe the presence of STH eggs in fecal samples of first- to third-grade students at SDN 23 Pasir Sebelah, located in Koto Tangah District, an area with historically high helminth infection rates. A descriptive cross-sectional design was used, involving total sampling of 124 students. Fecal specimens were examined microscopically using the direct smear method. Results showed that 6 students (6.9%) tested positive for STH eggs. The species identified included Ascaris lumbricoides (50%), Trichuris trichiura (40%), and hookworm (10%). Infections were more frequently found in male students and those aged 7–8 years. Most infected children demonstrated poor personal hygiene, particularly related to handwashing, nail cleanliness, and consistent use of footwear. In conclusion, the prevalence of STH infection among students at SDN 23 Pasir Sebelah was relatively low; however, inadequate personal hygiene remains a key contributing factor. Strengthening health education and promoting proper hygiene practices are essential to reduce the risk of STH transmission in school-aged children